Synthetic seeds and their role in agriculture: status and progress in sub-Saharan Africa - Mangena, Phetole (Plant Science Today, 2021)
Dicot seeds are commonly characterised by the rapid loss of moisture, vigour and longevity that cause adverse physiological and biochemical effects. Such changes reduce seed viability, germinability and seedling vigour in most agronomic legume crops. Thus, this paper evaluates the potential role of synthetic seed production as an avenue to achieve genetic variability, avert recalcitrance and fleet seed viability challenges experienced in recalcitrant legume species. Synthetic seeds, also known as synseeds or artificial seeds produced via somatic embryogenesis are crucial for the successful establishment of plants, and serve as an important determinant of plant productivity, especially for crops such as soybean. The potential use of synseeds could serve a fundamental role in ensuring cheap and rapid supply of new genetic resources and seed propagules for both breeders and farmers. This approach will ultimately maximise crop yield and offer a tremendous potential for micropropagation and germplasm preservation of recalcitrant species in sub-Saharan Africa. This review reports on a variety of applications and benefits of plant biotechnology in the African context and highlights important advantages such as genetic uniformity, simplified handling, storage, efficient distribution etc. that could be of immeasurable benefit to the seed value chain in agriculture, particularly for rural communities in these developing countries.